Sistem Informasi Administrasi Kependudukan Pada Kantor Distrik Merauke - Irawan, Andri; FML Dumatubun, Nelly (Jurnal Administrasi Karya Dharma, 2024)
This study aims to analyze the population administration information system (SIAK) application at the Merauke District Office based on Minister of Home Affairs Regulation No. 95 of 2019 concerning Population Administration Information Systems (SIAK). The method used in this study is a qualitative method using data collection techniques through interviews, observation, and documentation. Data were analyzed using interactive analysis which consisted of three stages namely; data condensation, data presentation, and drawing conclusions. The results of the study indicate that in general the application of SIAK at the Merauke District Office has not gone well and an orderly population administration has not been realized. Based on the indicators used, namely population data processing, presenting population data, and making population biodata, it can be seen in the data processing indicators that are still manual, in the data presentation indicators that are still not accurate, fast and on target and in the indicators of making population biodata, it is good in terms of utilization felt by the community but the services provided are still not effective and efficient. Supporting factors are the existence of facilities and infrastructure that are quite complete and the existence of a SIAK implementation budget from the local government. While the inhibiting factors are the low knowledge of employees/staff regarding SIAK and computer operation, there is no SIAK operator, the community does not understand the importance of having population data, and there are no regulations governing the implementation of SIAK at the Merauke District Office.